Imaging of Hockey-related Injuries of the Head, Neck, and Body - Holmes, R. Davis; Walsh, John P.; Yan, Yet Y.; Mallinson, Paul I.; Andrews, Gordon T.; Munk, Peter L.; Ouellette, Hugue A. (Seminars in Musculoskeletal Radiology, 2022)
Hockey is a demanding contact sport with growing popularity around the world. This article is part of a review series in this issue of Seminars in Musculoskeletal Radiology that summarizes epidemiological research on the patterns of ice hockey injuries as well as provides pictorial examples for a radiologist's perspective. We focus on non-extremity pathologies which encompass many of the most devastating injuries of hockey, namely those involving the head, neck, face, spine, and body.
Keywords: sports imaging; hockey; trauma; magnetic resonance imaging